PEMAHAMAN KELUARGA TERHADAP INTERVENSI RISIKO JATUH PADA PASIEN DEWASA DI RUANG RAWAT INAP RUMAH SAKIT SARI MULIA BANJARMASIN. - Muhammad Riduansyah; Peni Raswati; M Arief Wijaksono (CNJ: Caring Nursing Journal, 2021)
Falling patients are the most common incidents in hospital settings. Falling is a serious problem and requires high costs for patients and also for all health facilities. The incidence of a fall patient has a detrimental impact on the patient, namely the impact of physical injury. Fall Prevention is one of the indicators in Patient Safety. Family understanding of falling risk interventions in adult patients plays an important role in the implementation of patient safety, especially in preventing falling patients.Objective: To find a picture of family understanding of falling risk interventions in adult patients in the Sari Mulia Hospital Banjarmasin.Method: This research uses descriptive analytic method. Sampling is done by simple random sampling technique. The sample used was 41 families of adult patients in the Inpatient Room of Sari Mulia Hospital Banjarmasin. The analysis used in this study is univariate to analyze family understanding of falling risk interventions in patients.Results: The results of this study showed a good family understanding of 37 people (90.2%) and a sufficient family understanding of 4 people (9.8%). Conclusion: Good family understanding of falling risk interventions in adult patients in the Inpatient Room of Sari Mulia Hospital Banjarmasin.